2012
DOI: 10.1063/1.3673637
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal and acoustic noise interferences in low stiffness atomic force microscope cantilevers and characterization of their dynamic properties

Abstract: The atomic force microscope (AFM) is a powerful tool for the measurement of forces at the micro/nano scale when calibrated cantilevers are used. Besides many existing calibration techniques, the thermal calibration is one of the simplest and fastest methods for the dynamic characterization of an AFM cantilever. This method is efficient provided that the Brownian motion (thermal noise) is the most important source of excitation during the calibration process. Otherwise, the value of spring constant is underesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Boudaoud et al verified the impact of the ground vibrations and acoustic noise on the thermal method, as it is very sensitive technique and presence of certain noise may be a source of significant fraction of error [110]. They showed, that at the temperatures 22 o C and higher, the acoustic waves have more significant impact on the soft cantilevers (k<0.1 N/m), than the ground movement in particular, in noisy environment, where the acoustic noise exceeds 30 dB level at the 1 kHz-20 kHz bandwidth.…”
Section: Thermal Noise Methodsmentioning
confidence: 99%
“…Boudaoud et al verified the impact of the ground vibrations and acoustic noise on the thermal method, as it is very sensitive technique and presence of certain noise may be a source of significant fraction of error [110]. They showed, that at the temperatures 22 o C and higher, the acoustic waves have more significant impact on the soft cantilevers (k<0.1 N/m), than the ground movement in particular, in noisy environment, where the acoustic noise exceeds 30 dB level at the 1 kHz-20 kHz bandwidth.…”
Section: Thermal Noise Methodsmentioning
confidence: 99%
“…This uncertainty is mainly due to the fabrication process and leads to uncertain quantitative force measurements. As such, the stiffness calibration of AFM cantilevers has for many years been an open research field [42][43][44][45]. One of the widely used calibration methods is the so-called thermal calibration .…”
Section: Force Measurementmentioning
confidence: 99%
“…In (Boudaoud et al [2011]) and (Boudaoud et al [2012]), a detailed study on environmental noises and their effect on the positioning resolution of micromanipulation systems is performed. Three main sources of noise have been studied: cultural noises (ground vibrations), acoustic noises and thermal noises.…”
Section: Noise Influencesmentioning
confidence: 99%
“…The thermal noise is often considered as the main limitation of the positioning resolution in MEMS. In (Boudaoud et al [2012]), it has been found that the positioning resolution of AFM (Atomic Force Microscopy) based microgrippers is ranging from 365 pm to 675 pm. It is shown that resolutions are limited by both thermal and acoustic noises.…”
Section: Noise Influencesmentioning
confidence: 99%
See 1 more Smart Citation